Tradisi Membuatan Sandung Pada Umat Hindu Kaharingan Dayak Ngaju - Sihung, Sihung; Dharmawan, I Gusti Agung (Jayapangus Press, 2026)
Sandung is a distinctive structure in the Hindu Kaharingan tradition of the Dayak Ngaju community, serving as a repository for the bones of deceased family members following the tiwah ceremony. This tradition continues to exist today and reflects both cultural identity and religious belief. The purpose of this study is to describe the meaning, functions, and values embodied in the construction of sandung, while also examining how the tradition is maintained amidst social change. The research employed a qualitative descriptive method using both primary and secondary data sources. Primary data were obtained through in-depth interviews with six key informants and discussions with community members knowledgeable about the tradition, while secondary data were collected from documentation and related studies. Data collection involved observation, interviews, and documentation with customary leaders, community figures, and Hindu Kaharingan practitioners. The findings indicate that the construction of sandung requires specific skills, adherence to customary norms, and deep spiritual understanding. Beyond its role as a bone repository, sandung embodies profound social and religious meanings: it represents filial responsibility toward deceased parents, gratitude and respect for ancestors, and a medium for maintaining harmony between the living and the dead. The study concludes that the sandung tradition plays a vital role in strengthening the cultural identity of the Dayak Ngaju community, preserving the spiritual values of Hindu Kaharingan, and is believed to bring prosperity to surviving family members. Therefore, the continuity of this tradition requires collective support from society and younger generations to ensure its preservation.